Wafer‐Scale Single‐Crystalline AB‐Stacked Bilayer Graphene. Issue 37 (14th July 2016) - Nguyen, Van Luan; Perello, David J.; Lee, Seunghun; Nai, Chang Tai; Shin, Bong Gyu; Kim, Joong‐Gyu; Park, Ho Yeol; Jeong, Hu Young; Zhao, Jiong; Vu, Quoc An; Lee, Sang Hyub; Loh, Kian Ping; et al.
Abstract : Single‐crystalline artificial AB‐stacked bilayer graphene is formed by aligned transfer of two single‐crystalline monolayers on a wafer‐scale. The obtained bilayer has a well‐defined interface and is electronically equivalent to exfoliated or direct‐grown AB‐stacked bilayers.